250 Jahre öffentlich: die Badische Landesbibliothek 1771-2021 - Hiller von Gaertringen, Julia; Probst, Veit; Stello, Annika; Syré, Ludger (Lindemanns GmbH, 2021)
Begleitband zur Ausstellung, Badische Landesbibliothek, 16.11.2021-30.12.2021, Karlsruhe